P‐13.13: Influence of Thin Film Encapsulation (TFE) on Wide Angle Deviation (WAD) in Organic Light Emitting Diode (OLED) Display. (26th August 2021) - Xiao, Alex; Fu, JIAJIA; Liu, Yang
Abstract : In this paper, the influence of the initial chemical vapor deposition(1 st CVD) layer of thin film encapsulation (TFE) on wide angle deviation (WAD) in organic light emitting diode (OLED) display is studied. Just noticeable color difference (JNCD) defines the performance of WAD on OLED display. Film thickness and refractive index of the 1 st CVD layer of TFE are crucial to JNCD.The experimental data on Generation 6 substrate shows that small and uniform JNCD of OLED display can be achieved by 3‐layer of 1 st CVD structure with layer1 of SiONx of 0.05um thickness and 1.50 refractive index(RI), layer2 of SiONx of 0.8 um thickness and 1.72 RI and layer 3 of SiONx of 0.08 um thickness and 1.53 RI. That is, the value of JNCD on wide angle deviation is less than 2JNCD.